Application of bioluminescence resonance energy transfer assays in primary mouse neuronal cultures - Hanh T.M. Hoang; Kiran George; Mohiuddin Ahmad (STAR Protocols, 2024)
Summary: Bioluminescence resonance energy transfer (BRET) is widely employed for real-time monitoring of G protein-coupled receptor activity, interactions, and trafficking in heterologous cell lines, yet its use in neuronal systems remains limited. Here, we present a protocol to apply BRET assays to primary neuronal cultures from mouse embryos. We describe steps and key concepts for generating plasmid constructs and lentivirus preparations, plating and lentiviral transduction of primary cultured neurons in 96-well plates, and BRET data collection and analysis.For complete details on the use and execution of this protocol, please refer to George et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.